Kajian Orientalis Ignaz Goldziher tentang Hadis dan Sunnah - Cucu Setiawati (JOURNAL OF QUR'AN AND HADITH STUDIES, 2018)
Moslem concider Hadith and Sunnah are the main sources of Islamic teachings which serve as explanations for the verses of the Qur’an. But Orientalists such as Ignaz Goldziher has different oppinion, distinguishing between hadith and sunnah. According to him the sunnah is seen as a revision of the customs that occurred even though it did not strengthen the overall meaning. While the hadith according to him is the result of the development of Islam in the fields of religion, politics, and sociology in the period of two centuries, namely the first and second centuries. Hadith is not an Islamic document in the early days of its growth but it is the product of letter generations, after the die Prophet Muhammad SAW. In addition, the hadith is also one product generated from the effects of Islamic power that occurred at its glory.